E-MODULE COMPUTER ACCOUNTING BASED PROJECT BASED LEARNING - Annisa Fatimah; Rika Wijayanti; Marlina Magdalena (Jurnal Ekonomi, 2023)
In the implementation of the teaching and learning process, educators have a number of alternative methods for knowledge transfer. Selected media and methods are used as tools for educators to be able to convey the material correctly, which is coherent, easy to understand, and also clearly conveyed. This study aims to design and conceptualize online learning to support lectures with a project approach. The Blended Method using the Learning Management System (LMS) developed by the State Polytechnic of Malang (Polinema) is integrated with the Project Based Learning (PjBL) approach which is relevant because it take advantage of the online teaching system for students who have native digital skills. Because it is based on digital applications, LMS also makes it easier for students to access all learning content from anywhere and anytime. The Blended Method of LMS and PjBL combines learning methods of exploration, interpretation, and synthesis to produce a product that strives to meet adaptive characteristics with the times. Through qualitative research methods, it is hoped that the results of this study can describe the implementation of the LMS and PjBL blended methods that meet the characteristics of self-contained, stand alone, self-instructional where students can study comprehensive learning resources independently, both with and without lecturer guidance. In addition, user-friendliness is one of the important characteristics that must be met so that learning media must be easy to understand, use, and use as widely as possible. This model does not only focus on value as the end result, but emphasizes how a team can solve the problem and finally produce a product. This approach allows students to gain invaluable experience by actively participating in working on their projects.